THE EFFECTIVENESS OF SAT (SELF-ASSESSMENT TEACHER) APPLICATION TO IMPROVE TEACHERS’ PROFESSIONALISM - FR. R. Dewi Astika Indah Sintawati; Hermanu Joebagio; Leo Agung (Proceeding of International Conference on Art, Language, and Culture, 2017)
Teachers are educational staff who have the main duty to educate, teach, train, and guide students to have readiness to face increasingly fierce global competition with other nations. Hence, the position of teachers as professionals is urgently important in the realization of the vision and mission of learning especially in the educational aspect where the teachers can fulfill their duties. Teachers require particular attention from the government and society, ultimately the government regulates the improvement of the quality of teachers or teachers nationally through Law No. 20 of 2003 on National Education System. The “TPA” (Teacher Performance Assessment) system is still implemented conventionally which gives tremendous influence on teacher professionalism. This study aims to determine the effectiveness of SAT applications (Self-Assessment Teacher) to improve the teachers’ professionalism. This research uses quantitative methodology with independent t test using control class and experiment class as research samples. The result of this research revealed that a computer based SAT (Self-Assessment Teacher) application containing component of assessment which are personality competence, pedagogic competence, professional competence, social competence and result of assessment recap could maximally increase professionalism of teachers. The results indicated that the application was utilized effectively in improving the professionalism of teachers. In the application effectiveness test, it is known that the average value obtained by the experimental class is 82,9178, and that average value is higher than the control class 61,6363. This application is designed using the Dephi programming language and MySql database. The results of the teacher's performance appraisal can be viewed directly by the assessor and also the teacher with the login their user name and password in order to know the value of each competitor and the follow-up, and also the overall “TPA” recap value to the value used for the teacher's “PAK” (Credit Score Assessment).